2022
DOI: 10.3390/su142114473
|View full text |Cite
|
Sign up to set email alerts
|

Application of Unmanned Aerial Vehicles in Logistics: A Literature Review

Abstract: The booming development of e-commerce has brought many challenges to the logistics industry. To ensure the sustainability of the logistics industry, the impact of environmental and social sustainability factors on logistics development needs to be considered. Unmanned Aerial Vehicles (UAVs)/drones are used in the logistics field because of their flexibility, low cost, environmental protection and energy-saving advantages, which can achieve both economic benefits and social benefits. This paper reviews 36 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…For example, package delivery, the carrying of critical medical supplies to remote or inaccessible areas, or even aerotaxis capable of carrying passengers are some of the application areas where UAS offer great potential. Overall, UAS can provide advanced features against conventional solutions in logistics services, such as simultaneous delivery at several locations, reduced operational costs, environmental benefits, reduced traffic congestion and risk for accidents within large cities, and accessibility to remote areas or areas without infrastructures [57].…”
Section: Logistics and Delivery Of Goodsmentioning
confidence: 99%
“…For example, package delivery, the carrying of critical medical supplies to remote or inaccessible areas, or even aerotaxis capable of carrying passengers are some of the application areas where UAS offer great potential. Overall, UAS can provide advanced features against conventional solutions in logistics services, such as simultaneous delivery at several locations, reduced operational costs, environmental benefits, reduced traffic congestion and risk for accidents within large cities, and accessibility to remote areas or areas without infrastructures [57].…”
Section: Logistics and Delivery Of Goodsmentioning
confidence: 99%
“…Additionally, Yakushiji et al [15] demonstrated, with experiments using rotatory wing drones, that blood can be transported over long distances without evidence of hemolysis. In the context of medical , we can also cite the works reported in [1,2]. These authors presented a UAV-based delivery solution for blood products, vaccines, or medicines to rural and inaccessible regions.…”
Section: Related Workmentioning
confidence: 99%
“…A potential topic that has been widely explored in related research is the use of UAVs for humanitarian missions. They can be helpful in urgent areas of global public health because they can transport lightweight payloads such as medical tests, blood products, vaccines, or medicines to rural and inaccessible regions [1,2].UAVs can also help to save the lives of disaster victims due to their high speed and accessibility to remote and disconnected zones [3]. During disaster situations, UAVs can be employed to distribute humanitarian aid, survey damage, map survivors, and streamline service delivery [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sidekick delivery uses main vehicles, usually trucks, which carry sidekicks and parcels to local areas, where the sidekicks complete delivery. Drones, or Unmanned Aerial Vehicles (UAVs) [51], have evolved from military applications tracing back to the 1930s. As their costs have substantially decreased, they have become readily available to the public and logistics companies in the last 10 years [111].…”
Section: Sidekicksmentioning
confidence: 99%